Educational Games for Handling Trauma Healing in Post-Corona Virus Pandemic for Grade 2 Elementary Schools: Thematic 2 (Playing in My Neighborhood) - Yanuarsari, Dzuha Hening; Mukaromah, Mukaromah; Khamadi, Khamadi (International Conference on Elementary Education, 2021)
The coronavirus pandemic (2019) has had a significant impact on the world of education, especially in the teaching and learning process. One of the handlings of trauma-healing problems in children after the coronavirus pandemic is through playing while learning. In the second thematic book for grade 2 elementary school children with the theme of playing in my environment, this attracted the attention of researchers to make learning media innovations for children that were interesting and informative. Besides, factual learning media are the focus of researchers to provide new information for children. The purpose of this research is to produce game innovations that hone the cognitive and psychomotor aspects of children as learning media. This game contains educational information about the coronavirus using a persuasive approach. The method used in this research is using the Research and Development Method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The output in this research is an educational game that can deal with trauma healing for children after the coronavirus pandemic and can be used as a reference for the learning curriculum for grade 2 elementary school children.